Temuan Kubur di Situs Bawahparit (Limapuluh Koto) Corak Penguburan Megalitik Masa Transisi - Lutfi Yondri (Berkala Arkeologi Sangkhakala, 2011)
AbstractsBuried is one of some activities in human life, which have been doing if someone died. In Indonesia, since arrival of Islamic influence, the prehistoric buried in several places have been developed and change with new phenomenon. In other site, some places have indication with two signs of prehistoric and Islamic buried. That facts, we can find in Bawahparit site that have location on Kototinggi District, Limapuluhkoto regent’s, West Sumatera. In this site, we could find a hundred of the up right stones as a sign of buried and human skeletons were setting in cavity and putting down in northwest-southeast orientation. It is the same with Islamic buried.